Modified plastic particles and application of modified plastic particles in wrapping hot melting plastic iron component
By using modified plastic particles, the problems of poor film-forming performance and poor anti-corrosion treatment of iron components in powder coating technology are solved, and high-performance melt-plastic film layers and environmentally friendly hot-melt plastic iron component applications are realized.
Patent Information
- Application Number
- CN202411451532.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing powder coating technology has high requirements for the film forming performance of plastic particles. Poor film forming performance will lead to uneven coating thickness and poor anti-corrosion treatment effect on iron components.
Using modified plastic particles, this particle consists of polyvinyl chloride, nano -silica oxide, hydroxyl silicone oil, silicon wax, epoxy silicane puppet, stabilizer and pigment. After melting, the mixed effect of the auxiliary in the PVC substrate is improved.
It significantly improves the abrasion resistance, mechanical performance, low temperature, weather resistance and adhesion of the melting film layer, reducing zinc loss and environmental pollution, and no need to contain chromium passivation solution for anticorrosive and passivation treatment.
Smart Images

Figure BDA0005089274840000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder plastic dipping materials and their applications, and in particular relates to modified plastic particles and applications of the particles for wrapping hot-melt plastic iron components. Background Art
[0002] Dip molding is a plastic coating process, also known as coating, hot dip molding, hot compress coating, hot melt molding, etc. According to the different raw materials used for dipping molding, it can be divided into liquid dipping molding and powder coating (melt molding). Liquid dipping molding is to immerse the pretreated heated workpiece into the plastic liquid, and then dry and solidify it. However, liquid dipping molding requires the preparation of plastic liquid and high-temperature baking in advance, which consumes high energy and is difficult to control the thickness of the coating. For example, CN 113683844A discloses a high-toughness polyvinyl chloride steel skeleton dipping liquid and a dipping method thereof. A dipping liquid composed of a high-polymerization degree PVC paste resin, a low-polymerization degree PVC paste resin, a plasticizer, a calcium-zinc composite stabilizer, a cross-linking agent, a viscosity reducer, a defoaming agent and an inorganic additive is used, and a high-toughness dip-molded product is obtained by dipping and drying.
[0003] Powder coating is to add the heated workpiece into plastic particles or to coat the plastic particles so that the heated workpiece is in full contact with the plastic particles. The plastic particles melt at high temperature on the surface of the heated workpiece to form a film, thereby forming a plastic anti-corrosion and anti-rust coating. Powder coating is gaining more and more attention due to its low energy consumption and simple control of coating thickness. However, powder coating has high requirements on the film-forming properties of plastic particles. Poor film-forming properties will lead to uneven coating thickness. In addition, for the currently commonly used iron components, hot-dip galvanizing is generally required for anti-corrosion treatment. Therefore, the adhesion of the molten plastic film layer to the galvanized layer will directly affect the treatment effect of hot-melt plastic.
[0004] At present, the commonly used plastic particles for powder coating mainly include polyvinyl chloride, polyethylene, thermoplastic polyurethane, thermoplastic polyester, etc. Polyvinyl chloride has the advantages of good adhesion and good corrosion resistance, but its low temperature resistance and weather resistance are slightly poor. Polyethylene has the advantages of high strength and good cold resistance, but the lack of polar groups has poor adhesion. Thermoplastic polyurethane and thermoplastic polyester have the advantages of good adhesion and high strength, but there are problems of slightly poor flexibility or weather resistance and high cost. CN 114773919A discloses a thermoplastic polyethylene powder coating and its dipping process, including polyethylene with a mass fraction of 92% and an auxiliary agent with a mass fraction of 8%, wherein the auxiliary agent includes a glue with a mass fraction of 6% and a masterbatch with a mass fraction of 2%. By adding a specific glue auxiliary agent, high adhesion between thermoplastic polyethylene powder and galvanized workpieces is achieved. CN 102485816 A discloses a thermoplastic powder coating, which is composed of polyvinyl chloride, a plasticizer, a heat stabilizer, a nano-scale inorganic filler, and a powder auxiliary agent. By using triphenyl phosphate, diethylene glycol phthalate and dibutyl tin monobutyl maleate as plasticizers and thermal stabilizers, the addition performance, flexibility and heat resistance of polyvinyl chloride powder are significantly improved. However, the above additives have limited effect on improving the mechanical properties of polyvinyl chloride. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a modified plastic particle.
[0006] Another object of the present invention is to provide a method for preparing the modified plastic particles.
[0007] Another object of the present invention is to provide an application of the modified plastic particles mentioned above to wrap hot-melt plastic iron components.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A modified plastic particle, composed of the following components in parts by weight:
[0010] 100 parts of polyvinyl chloride (PVC), 10-20 parts of nano silicon dioxide, 5-15 parts of hydroxy silicone oil, 4-8 parts of silicone wax, 3-6 parts of epoxy silane coupling agent, 0.2-5 parts of stabilizer, and 0-5 parts of pigment.
[0011] Preferably, the nano-silicon dioxide refers to precipitated silicon dioxide with a particle size of 20 to 100 nm. The precipitated silicon dioxide used in the present invention has the advantages of low cost and good processing performance. Nano-silicon dioxide as a filler for the PVC substrate can improve the wear resistance and mechanical properties of the melt-molded film layer. At the same time, as a condensation reaction carrier of hydroxyl silicone oil and epoxy silane coupling agent in the present invention, it can improve the mixing effect of hydroxyl silicone oil and epoxy silane coupling agent in the PVC substrate and improve the mechanical properties of the melt-molded film layer.
[0012] Preferably, the hydroxy silicone oil refers to a hydroxy silicone oil with a viscosity of 50 to 500 mPa·s and a hydroxy content of 1% to 5%. The present invention improves the low-temperature flexibility and weather resistance of PVC by adding hydroxy silicone oil.
[0013] Preferably, the silicone wax refers to silicone wax with a softening point of 45 to 60° C., such as DY-801 silicone wax and DY-803 silicone wax from Dayi Chemical. The present invention improves the lubricity and film-forming properties of PVC by adding silicone wax, and improves the mixing effect of hydroxy silicone oil and epoxy silane coupling agent in PVC.
[0014] Preferably, the epoxysilane coupling agent refers to KH-560 (γ-glycidyloxypropyltrimethoxysilane) or KH-561 (γ-glycidyloxypropyltriethoxysilane). The present invention introduces epoxy groups by adding epoxysilane coupling agent to improve the adhesion between the melt-molded film layer and the galvanized workpiece, and on the other hand, as a coupling agent and cross-linking agent for nano-silicon dioxide and hydroxyl silicone oil, it can improve the mixing effect of nano-silicon dioxide and hydroxyl silicone oil in the PVC substrate, reduce the precipitation of hydroxyl silicone oil, and improve the comprehensive performance of the melt-molded film layer.
[0015] Preferably, the stabilizer is dibutyltin dilaurate. The present invention can improve the heat resistance of PVC by adding dibutyltin dilaurate as a stabilizer, and can be used as a catalyst for the condensation cross-linking reaction of hydroxy silicone oil and epoxy silane coupling agent, and can significantly improve the mixing effect of hydroxy silicone oil in PVC substrate through coupling with nano silicon dioxide, reduce the precipitation of hydroxy silicone oil, and improve the comprehensive performance of melt-molded film layer.
[0016] Preferably, the pigment is titanium dioxide, iron oxide powder or carbon black.
[0017] The preparation method of the modified plastic particles comprises the following preparation steps:
[0018] (1) Pour nano-silica, hydroxy silicone oil, silicone wax, epoxy silane coupling agent and pigment into a mixing tank, stir and mix them evenly to obtain a mixing aid;
[0019] (2) Adding PVC pellets and stabilizer into an extruder, heating and melting, then adding the mixing aid of step (1), mixing, extruding and granulating, and crushing to obtain modified plastic particles.
[0020] In the preparation method of the present invention, by pre-mixing nano-silica, hydroxyl silicone oil, silicone wax, epoxy silane coupling agent and pigment, the coupling and cross-linking effects of nano-silica, hydroxyl silicone oil and epoxy silane coupling agent can be significantly improved, thereby improving the mixing and dispersion effect of the above-mentioned additives in the PVC substrate and improving the comprehensive performance of the melt-plastic film layer.
[0021] Application of the modified plastic particles wrapped in hot-melt plastic iron components.
[0022] Preferably, the application method is: heating the hot-dip galvanized iron component to 150-200°C, then immersing it in a fluidized bed containing the above-mentioned modified plastic particles, so that the modified plastic particles are uniformly adhered to the surface of the iron component and melted into a film, and then cooling to obtain a hot-melt plastic iron component.
[0023] Preferably, the hot-dip galvanizing treatment refers to first immersing the iron component in a plating-assisting solvent, performing the plating-assisting treatment at a temperature of 40 to 70° C. for 30 seconds to 5 minutes, taking it out and drying it, then immersing it in a hot-dip galvanizing solution for hot-dip plating, taking it out and cooling it to obtain the iron component after the hot-dip galvanizing treatment; the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0024] Zinc chloride 80-150g / L, zinc acetate 60-120g / L, acetic acid 10-30g / L, cyclodextrin 5-20g / L;
[0025] The hot-dip galvanizing liquid is pure zinc liquid or zinc liquid added with trace elements; the trace elements are at least one of rare earth elements, aluminum, silicon, and tin; the amount of the trace elements added is 0.1% to 5% of the mass of the zinc liquid; the temperature of the hot-dip galvanizing is 450 to 550°C.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The modified plastic particles of the present invention use low-cost PVC as the main raw material, and improve the wear resistance and mechanical properties by adding nano-silicon dioxide; improve the low-temperature flexibility and weather resistance by adding hydroxy silicone oil; improve the lubricity and film-forming properties by adding silicone wax; improve the adhesion by adding epoxy silane coupling agent; and improve the system compatibility through the mutual synergistic effect and chemical reaction of each component. The obtained modified plastic particles have good comprehensive properties.
[0028] (2) The modified plastic particles of the present invention further use dibutyltin dilaurate as a heat stabilizer for PVC to improve the high-temperature processing stability of PVC. At the same time, it is a catalyst for the condensation cross-linking reaction of hydroxy silicone oil and epoxy silane coupling agent, which can significantly improve the modification effect of the melt-molded film layer.
[0029] (3) The preparation method of the present invention can significantly improve the mixing and dispersion effect of the modified additives in the PVC substrate and improve the comprehensive performance of the melt-plastic film layer through the pre-mixing reaction of the mixing additives.
[0030] (4) The use of the modified plastic particles of the present invention to wrap the hot-melt plastic iron components can eliminate the need for anti-corrosion passivation treatment using a chromium-containing passivation solution, thereby reducing environmental pollution.
[0031] (5) In the application process of the modified plastic particles of the present invention to wrap the hot-melt plastic iron components, a plating-assisting solvent with a specific composition is used for plating-assisting treatment, which can reduce zinc loss and improve the hot-dip galvanizing effect. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0033] Example 1
[0034] A modified plastic particle, composed of the following components in parts by weight:
[0035] 100 parts of PVC pellets, 16 parts of precipitated silica (particle size 50-60nm), 10 parts of hydroxy silicone oil (viscosity 200mPa·s, hydroxyl content 1.6wt%), 6 parts of silicone wax (DY-803 silicone wax), 4 parts of epoxy silane coupling agent KH-560, and 2 parts of dibutyltin dilaurate.
[0036] The preparation method of the modified plastic particles comprises the following preparation steps:
[0037] (1) Pour precipitated silica, hydroxy silicone oil, silicone wax, and epoxy silane coupling agent into a mixing tank, stir them thoroughly for 1 hour at room temperature to mix them evenly, and obtain a mixing aid.
[0038] (2) Add PVC pellets and dibutyltin dilaurate into an extruder, heat and melt at 160-180° C., then add the mixing aid of step (1), mix, extrude and granulate, and crush to obtain modified plastic pellets.
[0039] The specific application method of the modified plastic particles wrapped in hot-melt plastic iron components is as follows:
[0040] 1) The iron component after cleaning and rust removal is immersed in a plating-assisting solvent (the plating-assisting solvent is an aqueous solution containing the following concentration components: 120 g / L zinc chloride, 90 g / L zinc acetate, 20 g / L acetic acid, and 10 g / L cyclodextrin), and the plating-assisting treatment is carried out at 55° C. for 90 seconds. After being taken out, it is dried at 120° C. for 3 minutes, and then immersed in a 490° C. hot-dip galvanizing solution (composed of 0.18 wt% aluminum and 98.2 wt% zinc) for hot-dip plating for 1 minute until zinc ash and carbides float on the surface of the zinc solution. After being taken out, it is cooled in a water bath to obtain the iron component after hot-dip galvanizing.
[0041] 2) The hot-dip galvanized iron component is placed in a heating furnace and heated to 180°C, and then immersed in a fluidized bed containing the above-mentioned modified plastic particles, so that the modified plastic particles are uniformly adhered to the surface of the iron component and melted into a film (fluidized bed coating method). By controlling the modified plastic particle powder concentration and the immersion time in the fluidized bed, the thickness of the hot-melt plastic film layer is controlled to be 0.7±0.05mm, and the hot-melt plastic iron component is obtained after cooling.
[0042] Example 2
[0043] A modified plastic particle, composed of the following components in parts by weight:
[0044] 100 parts of PVC pellets, 10 parts of precipitated silica (particle size 50-60nm), 5 parts of hydroxy silicone oil (viscosity 50mPa·s, hydroxyl content 3.0wt%), 4 parts of silicone wax (DY-803 silicone wax), 3 parts of epoxy silane coupling agent KH-560, 0.5 parts of dibutyltin dilaurate, and 1 part of titanium dioxide.
[0045] The preparation method of the modified plastic particles and the application of wrapping hot-melt plastic iron components are the same as those in Example 1.
[0046] Example 3
[0047] A modified plastic particle, composed of the following components in parts by weight:
[0048] 100 parts of PVC pellets, 20 parts of precipitated silica (particle size 50-60nm), 15 parts of hydroxy silicone oil (viscosity 500mPa·s, hydroxyl content 1.1wt%), 8 parts of silicone wax (DY-801 silicone wax), 16 parts of epoxy silane coupling agent KH-56, and 3 parts of dibutyltin dilaurate.
[0049] The preparation method of the modified plastic particles and the application of wrapping hot-melt plastic iron components are the same as those in Example 1.
[0050] Example 4
[0051] A modified plastic particle, compared with Example 1, uses an equal amount of stabilizer tribasic lead sulfate to replace dibutyltin dilaurate, and the rest is the same.
[0052] Example 5
[0053] A modified plastic particle, compared with Example 1, uses an equal amount of stabilizer calcium stearate to replace dibutyltin dilaurate, and the rest is the same.
[0054] Example 6
[0055] A modified plastic particle, whose component composition is the same as that of Example 1, and the preparation method of the modified plastic particle is as follows:
[0056] The PVC pellets and stabilizer dibutyltin dilaurate are added to the extruder and heated to melt at 160-180°C, and then nano-silicon dioxide, hydroxy silicone oil, silicone wax, and epoxy silane coupling agent are added in sequence, mixed, extruded, granulated, and crushed to obtain modified plastic particles.
[0057] Comparative Example 1
[0058] A modified plastic particle, compared with Example 1, no hydroxy silicone oil is added, and the rest is the same.
[0059] Comparative Example 2
[0060] A modified plastic particle, compared with Example 1, without adding silicone wax, and the rest is the same.
[0061] Comparative Example 3
[0062] A modified plastic particle, compared with Example 1, without adding epoxy silane coupling agent KH-560, and the rest is the same.
[0063] The tensile strength, elongation at break, coating adhesion performance, coating resistance to low-temperature embrittlement (using low-temperature impact performance test), and coating weather resistance (tensile strength retention rate) of the hot-melt plastic film layers obtained in the above Examples 1 to 6 and Comparative Examples 1 to 3 were tested (the above performance tests refer to standard JT / T600.2-2004, Thermoplastic Polyethylene Powder Coatings and Coatings), and the results are shown in Table 1 below.
[0064] Table 1
[0065]
[0066] It can be seen from the results in Table 1 that the present invention can significantly improve the strength, toughness, adhesion, low temperature resistance and weather resistance of the obtained PVC hot melt plastic film layer by adding hydroxy silicone oil, silicone wax, epoxy silane coupling agent and nano silicon dioxide. At the same time, it can be seen from the comparison results of Examples 4 to 5 with Example 1 that the use of a specific dibutyltin dilaurate as a heat stabilizer for PVC can further improve the mechanical properties and weather resistance of the hot melt plastic film layer compared with other heat stabilizers. The reason is that dibutyltin dilaurate has the effect of catalyzing the dealcoholization condensation crosslinking reaction of hydroxy silicone oil and epoxy silane coupling agent, which can significantly improve the polymer cohesive strength and improve the mixing improvement effect of hydroxy silicone oil in the PVC matrix. It can be seen from the comparison results of Example 6 with Example 1 that by pre-mixing nano silicon dioxide, hydroxy silicone oil, silicone wax and epoxy silane coupling agent, the mixing and dispersion effect of the modification aid in the PVC substrate can be significantly improved, and the comprehensive performance of the melt plastic film layer can be improved.
[0067] Comparative Example 4
[0068] Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0069] Zinc chloride 120g / L, ammonium chloride 120g / L.
[0070] The rest is the same as Example 1.
[0071] Comparative Example 5
[0072] Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0073] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L.
[0074] The rest is the same as Example 1.
[0075] Comparative Example 6
[0076] Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0077] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L, chitosan 10g / L.
[0078] The rest is the same as Example 1.
[0079] Comparative Example 7
[0080] Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0081] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L, surfactant OP-10 10g / L.
[0082] The rest is the same as Example 1.
[0083] The thickness of the galvanized layer of the iron component after hot-dip galvanizing treatment obtained in step 1) of the above Example 1 and Comparative Examples 4 to 7 (the magnetic thickness gauge detects 10 different sites and takes the average value), adhesion (refer to Appendix L of DL / T5358-2006, thermal spray coating bonding strength test method, observe with a 4x magnifying glass, no coating peels off from the substrate, proving that the adhesion is good), coating uniformity (refer to Appendix A of GB / T2694-2018 Hot-dip galvanizing layer uniformity test, copper sulfate test method, record the number of corrosion resistance), corrosion resistance (refer to GB / T 10125, artificial atmosphere corrosion test salt spray test, acetic acid salt spray (AASS) after 240h The percentage of corrosion area accounts for the total area) and zinc loss rate (mainly the loss of zinc ash and bottom slag, calculated as: total weight of consumed hot-dip galvanizing liquid-actual galvanizing layer calculated weight / total weight of hot-dip galvanizing liquid) were tested, and the smoke generation during the hot-dip galvanizing process was observed. The results are shown in Table 2 below.
[0084] Table 2
[0085] Test sample thickness Adhesion Coating uniformity Corrosion resistance Zinc loss rate Smoke situation Example 1 106μm No peeling 11 times 8.6% 6.72% Basically smoke-free Comparative Example 4 115μm No peeling 6 times 18.2% 11.80% Lots of smoke Comparative Example 5 112μm No peeling 6 times 14.7% 9.26% Basically smoke-free Comparative Example 6 108μm No peeling 7 times 13.4% 8.59% Basically smoke-free Comparative Example 7 106μm No peeling 7 times 15.1% 8.85% Basically smoke-free
[0086] It can be seen from the results in Table 2 that the use of the plating solvent of the present invention can significantly improve the uniformity and corrosion resistance of the coating, and can significantly reduce the zinc loss rate and significantly reduce the generation of hot-dip galvanizing smoke compared to conventional zinc chloride and ammonium chloride plating solvents. In addition, it can be seen from the results of Comparative Examples 5 to 7 that the addition of cyclodextrin has a very significant effect on improving the uniformity and corrosion resistance of the coating, and can further reduce the zinc loss rate. Compared with conventional surfactants and crystallization film-forming aids such as chitosan, the use of cyclodextrin as a crystallization film-forming aid in the present invention has obvious advantages.
[0087] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A modified plastic particle, characterized in that: It is composed of the following components in parts by weight: 100 parts of polyvinyl chloride, 10-20 parts of nano silicon dioxide, 5-15 parts of hydroxy silicone oil, 4-8 parts of silicone wax, 3-6 parts of epoxy silane coupling agent, 0.2-5 parts of stabilizer, and 0-5 parts of pigment.
2. A modified plastic particle according to claim 1, characterized in that: The nano-silicon dioxide refers to precipitated silicon dioxide with a particle size of 20 to 100 nm.
3. The modified plastic particles according to claim 1, characterized in that: The hydroxy silicone oil refers to a hydroxy silicone oil with a viscosity of 50 to 500 mPa·s and a hydroxyl content of 1% to 5%.
4. The modified plastic particles according to claim 1, characterized in that: The silicone wax refers to silicone wax having a softening point of 45 to 60°C.
5. The modified plastic particles according to claim 1, characterized in that: The epoxy silane coupling agent refers to KH-560 or KH-561.
6. The modified plastic particles according to claim 1, characterized in that: The stabilizer is dibutyltin dilaurate.
7. A method for preparing modified plastic particles according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: (1) Pour nano-silica, hydroxy silicone oil, silicone wax, epoxy silane coupling agent and pigment into a mixing tank, stir and mix them evenly to obtain a mixing aid; (2) adding PVC pellets and stabilizer into an extruder, heating and melting, then adding the mixing aid of step (1), mixing, extruding and granulating, and crushing to obtain modified plastic particles.
8. Use of the modified plastic particles described in any one of claims 1 to 6 to wrap hot-melt plastic iron components.
9. The use of modified plastic particles to wrap hot-melt plastic iron components according to claim 8, characterized in that: The application method is: heating the hot-dip galvanized iron component to 150-200°C, then immersing it in a fluidized bed containing the modified plastic particles described in any one of claims 1 to 4, so that the modified plastic particles are uniformly adhered to the surface of the iron component and melted to form a film, and then cooling to obtain a hot-melt plastic iron component.
10. The use of modified plastic particles to wrap hot-melt plastic iron components according to claim 9, characterized in that: The hot-dip galvanizing treatment refers to first immersing the iron component in a plating-assisting solvent, performing the plating-assisting treatment at a temperature of 40 to 70° C. for 30 seconds to 5 minutes, drying after taking it out, and then immersing it in a hot-dip galvanizing solution for hot-dip plating, taking it out and cooling it to obtain the iron component after the hot-dip galvanizing treatment; the plating-assisting solvent is an aqueous solution containing the following concentration components: Zinc chloride 80-150g / L, zinc acetate 60-120g / L, acetic acid 10-30g / L, cyclodextrin 5-20g / L; The hot-dip galvanizing liquid is pure zinc liquid or zinc liquid added with trace elements; the trace elements are at least one of rare earth elements, aluminum, silicon, and tin; the amount of the trace elements added is 0.1% to 5% of the mass of the zinc liquid; the temperature of the hot-dip galvanizing is 450 to 550°C.
Citation Information
Patent Citations
Novel thermoplastic powder coating
CN102485816A
Thermoplastic polyethylene powder coating and plastic dipping process thereof
CN114773919A
Dual-curing composition
CN103571211A
High-toughness polyvinyl chloride steel framework plastic dipping liquid and plastic dipping method thereof
CN113683844A
High-temperature-resistant insulating plastic dipping liquid and preparation method thereof
CN118374110A